Concentrações séricas de progesterona e metabólitos lipídicos em cabras mestiças alimentadas com dietas hiperlipídicas durante o ciclo estral - Uribe-Velásquez, Luis Fernando [UNESP]; Torres, Ciro Alexandre Alves; Valadares Filho, Sebastiäo de Campos; Cecon, Paulo Roberto (My University, 1997)
The serum concentration of progesterone and lipidics metabolites were studied using tallow as lipidic suplementation during the estrous cycle of 32 crossbred goats, with average age and weight of five months and 25 kg. The goats were randomlly allocated in four treatments as described: treatment 1, restricted intake; treatment 2, full feed; treatments 3 and 4, hiperlipidics diets with 2.5% and 5.0% of tallow, respectively. The female goats under restricted intake, showed the small serum progesterone level (P<0.05) at 0, 3, 6, 9 and 12 days of the estrous cycle, while the ones under hiperlipidics diets, treatments 3 and 4, showed greater levels. The same results were found for serum levels of cholesterol and HDL in the estrous cycle days 6, 9 and 21, and 12, 15 and 21, respectively, that is, the females under restricted diet showed the small level and the ones treated with hiperlipidics diets, the highest. The hiperlipidics diets were important factor in altering the serum cholesterol and HDL levels, showing that the lipidic metabolism may be effective in cyclic luteal progesterone production in the puberal female goats.

Estudou-se o efeito da suplementação lipídica, utilizando como fonte o sebo bovino, na concentração sérica de progesterona e metabólitos lipídicos durante o ciclo estral de 32 cabras mestiças, com idade e peso médio de cinco meses e 25 kg, distribuídas aleatoriamente em quatro tratamentos: tratamento 1, consumo restrito a 75% do recomendado; tratamento 2, consumo à vontade; tratamentos 3 e 4, dietas hiperlipídicas contendo 2,5% e 5,0% de sebo, respectivamente. As fêmeas submetidas a consumo restrito apresentaram as menores (P<0,05) concentrações séricas de progesterona nos dias 0, 3, 6, 9 e 12 do ciclo estral; enquanto as submetidas a dietas hipercalóricas, as maiores concentrações. O mesmo resultado foi encontrado na avaliação das concentrações séricas de colesterol e HDL nos dias 6, 9 e 21; e 12, 15 e 21 do ciclo em estudo, respectivamente, ou seja, as fêmeas submetidas a consumo restrito apresentaram as menores concentrações, e as de dieta hipercalórica, as maiores. As dietas hiperlipídicas foram importantes na modificação do colesterol e HDL, revelando que o metabolismo lipídico pode ter efeito na produção luteal cíclica de progesterona em cabras mestiças, púberes.
Serum concentrations of progesterone and lipidics metabolites of crossbred goats fed with hiperlipidics diets during estrous cycle
Keywords: Cholesterol; HDL; Hormonal profile; Tallow; Capra hircus